1978
DOI: 10.1149/1.2131535
|View full text |Cite
|
Sign up to set email alerts
|

Flatband Potentials and Donor Densities of Polycrystalline α ‐ Fe2 O 3 Determined from Mott‐Schottky Plots

Abstract: DICYANOAURATE 723 3. The proposed mechanism explains readily the features of the anodic dissolution of gold in alkaline cyanide electrolyte.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
211
2
1

Year Published

1986
1986
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 326 publications
(230 citation statements)
references
References 0 publications
16
211
2
1
Order By: Relevance
“…[29] This led to the hypothesis that two different types of p-type charge carriers (holes) could be produced in hematite, depending on the excitation mechanism, and were responsible for the observed difference in photoelectrochemical (PEC) performance as a function of wavelength. [30][31] However, the most recent ab initio calculations to determine the electronic structure of hematite by the HartreeFock approach [32] and density functional theory with a local spin-density approximation and coulomb correlation [33][34] both predict that the highest occupied energy states are primarily O p in character and the lowest unoccupied states are from an empty Fe d band. This conclusion is also supported by soft-Xray (O K-edge) absorption and emission spectroscopy, which, when compared to photoemission spectra from configurationinteraction FeO 6 cluster calculations, confirm that the valence band is at least strongly hybridized and indicates further that it is mostly of O 2p character.…”
Section: Optoelectronic Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…[29] This led to the hypothesis that two different types of p-type charge carriers (holes) could be produced in hematite, depending on the excitation mechanism, and were responsible for the observed difference in photoelectrochemical (PEC) performance as a function of wavelength. [30][31] However, the most recent ab initio calculations to determine the electronic structure of hematite by the HartreeFock approach [32] and density functional theory with a local spin-density approximation and coulomb correlation [33][34] both predict that the highest occupied energy states are primarily O p in character and the lowest unoccupied states are from an empty Fe d band. This conclusion is also supported by soft-Xray (O K-edge) absorption and emission spectroscopy, which, when compared to photoemission spectra from configurationinteraction FeO 6 cluster calculations, confirm that the valence band is at least strongly hybridized and indicates further that it is mostly of O 2p character.…”
Section: Optoelectronic Characteristicsmentioning
confidence: 99%
“…Typically, the capacitance is determined by fitting the frequency responses with a simple resistor-capacitor (RC) circuit model (see Figure 8 a). A single frequency, [30,50,56] multiple frequencies, [105] extrapolating to an infinite frequency, [54,57,126] or an entire range of high frequencies [65,[127][128] (for heavily doped samples) have been reported for both planar and structured electrodes. [24,[127][128] However since the classic MS relation relies on a simple parallel-plate capacitor model the application of EIS data from real systems has often been problematic.…”
Section: Advanced Understanding By Using Electrochemical Impedance Spmentioning
confidence: 99%
“…Another feature of the Mott-Schottky plot depicted in Figure 4a is the existence of a break at ≈ 0 V. This break of the plot was explained assuming the existence of two kinds of donors one very close to the conduction band and the other below the conduction band. 12 From the slope of the straight line of the C -2 vs. U plot, the donor and acceptor densities of the Fe and Cr oxide layers can be calculated. Using ε = 12 for the dielectric constant of chromium oxide and iron oxide, the values of N D and N A are respectively 0.5x10 20 and 2.3x10 20 cm -3 .…”
Section: Aisi 304 Stainless Steelmentioning
confidence: 99%
“…Hematite, α-Fe 2 O 3 , has a much more favorable 2.2 eV band gap for solar harvesting and therefore absorbs about 40% of the air mass 1.5 solar spectrum [6][7][8]. Previous researchers found that the energetic position of the valence band edge in hematite is appropriate for water oxidation [9][10][11][12][13][14][15][16][17][18][19][20][21]. In fact, iron oxides are amongst the smallest band gap semiconductors that are stable toward oxygen evolution and are certainly the least expensive of them.…”
Section: Introductionmentioning
confidence: 99%